Nurses Workload Comparison Between Voluntary Nurses and Government Employee Nurses - Hotma Royani Siregar; Febrina Angraini Simamora (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: Padangsidimpuan General Hospital is a hospital owned by the Padangsidimpuan City government which employs Voluntary Nurses and government Employee Nurses. The purpose of this study is to determine the workload comparison of Voluntary Nurses and Government Employee  Nurses. Methods: Research was conducted using quantitatif and qualitative methods using observation techniques work sampling, and interview guidelines. Partisipant has been observed were 15 Voluntary Nurses and 15 Government Employee nurses who are on duty at that time by using accidental sampling technique. Samples taken were all activities carried out by Voluntary Nurses and Government Employee Nurses, such as direct nursing activities, indirect nursing activities, personal activities, and non-productive activities. Results: The results of observations and interviews described there is difference between workload of voluntary nurses with government employee nurses. After analysed using Collaizi’s Methode and The mannwhitney test on the workload of nurses Voluntary Nurses and Government Employee  Nurses found a significant difference with the value of p = 0.0001 (p <0.05) which means there is a difference in workload between Voluntary Nurses and Government Employee  Nurses. With the workload on Voluntary nurses amounted to 74.8%, while the Government Employee  nurses amounted to 69.6%. The results of the study suggest that the management of Padangsidimpuan General Hospital to manage nursing staff optimally to achieve quality nursing services. Conclusions: There is difference in workload between Voluntary nurses and government employee nurses.